QSAR models for predicting the toxicity of piperidine derivatives against Aedes aegypti. Issue 6 (3rd June 2017) - Doucet, J. P.; Papa, E.; Doucet-Panaye, A.; Devillers, J.
Abstract: QSAR models are proposed for predicting the toxicity of 33 piperidine derivatives against Aedes aegypti . From 2D topological descriptors, calculated with the PaDEL software, ordinary least squares multilinear regression (OLS-MLR) treatment from the QSARINS software and machine learning and related approaches including linear and radial support vector machine (SVM), projection pursuit regression (PPR), radial basis function neural network (RBFNN), general regression neural network (GRNN) and k -nearest neighbours ( k -NN), led to four-variable models. Their robustness and predictive ability were evaluated through both internal and external validation. Determination coefficients ( r 2 ) greater than 0.85 on the training sets and 0.8 on the test sets were obtained with OLS-MLR and linear SVM. They slightly outperform PPR, radial SVM and RBFNN, whereas GRNN and k -NN showed lower performance. The easy availability of the involved structural descriptors and the simplicity of the MLR model make the corresponding model attractive at an exploratory level for proposing, from this limited dataset, guidelines in the design of new potentially active molecules.